2019
DOI: 10.7771/2157-9288.1208
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Teachers’ Positive and Practical Risk-Taking When Teaching Science Through Engineering Design

Abstract: for additional information. This is an Open Access journal. This means that it uses a funding model that does not charge readers or their institutions for access. Readers may freely read, download, copy, distribute, print, search, or link to the full texts of articles. This journal is covered under the CC BY-NC-ND license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…In the study conducted by Allmond et al (2016), it was observed that positive classroom cultures contribute to students' intellectual risk-taking behaviors. Radloff et al (2019), also in a study that included elementary school students, concluded that risktaking and the teacher's contributions both serve to increase students' participation in science courses and help develop their course-specific self-confidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study conducted by Allmond et al (2016), it was observed that positive classroom cultures contribute to students' intellectual risk-taking behaviors. Radloff et al (2019), also in a study that included elementary school students, concluded that risktaking and the teacher's contributions both serve to increase students' participation in science courses and help develop their course-specific self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Allmond et al (2016) demonstrated intellectual risk-taking behaviors to be among 21 st century skills and emphasized that it is necessary to support students in adopting such behaviors. Radloff et al (2019) also observed that the benefits of risk-taking included increased student participation in science courses, increased self-confidence in teachers about teaching science, and increased collaborative teacher relations. Studies conducted at middle school level have demonstrated that there is a low-level relation between test anxiety and intellectual risk-taking behavior (Bal-İncebacak et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 92%
“…But more than this, they need an open dialogue in their schools, a culture to be able to plan for risk taking and the ability to leverage a community to share best practice. As Radloff et al (2019) found there are four types of perceived risks which included practical, pedagogical, conceptual, and personal; these varied between different generations of teachers. Significantly, they found that the benefits of risk-taking include increased student engagement, improved self-confidence, and greater teacher collaboration across generations (Radloff et al, 2019).…”
Section: Leadership and Risk Takingmentioning
confidence: 99%
“…As Radloff et al (2019) found there are four types of perceived risks which included practical, pedagogical, conceptual, and personal; these varied between different generations of teachers. Significantly, they found that the benefits of risk-taking include increased student engagement, improved self-confidence, and greater teacher collaboration across generations (Radloff et al, 2019). Furthermore, Slavit et al (2016) highlight the power of doing and risk-taking in teacher development, particularly in the ways in which teacher collaboration advances curriculum and instruction.…”
Section: Leadership and Risk Takingmentioning
confidence: 99%
“…e advancement and innovation of traditional industries and technological progress in the enterprise have played an exciting role [5,6].…”
Section: Basic Connotation Of Industry Education Integrationmentioning
confidence: 99%